Analisis Penjalaran Retakan pada Pipa Transmisi Gas Jenis SUS 304 Menggunakan Metode Elemen Hingga - Asbar R (Jurnal Teknik Mesin Unsyiah, 2012)
A method developed to predict the failure that occurs at gas transmission pipe caused by loading with peak angle crack opening is described in this paper. There are two aspects become the main consideration; the maximum crack peak angle opening for the given load and space, and the determination of the critical stress intensity factor to search at what degree of loading the crack on the gas transmission pipe experiencing creep or failure. This research uses arc-shaped tension specimen and the analysis is carried out by finite element method using ansys ™ rel 5.4. In order to get the stress intensity factor, the loading is varied from 1 KN to 160 KN. Based on finite element method, the maximum stress intensity factor occurs at the range of loading of 16-160 KN, which is 5.67 x 1016 MPa.m1/2, and the minimum factor occurs at the range of loading of 0.5-1 KN, which is 3.76 MPa.m1/2. The stress intensity factor result is also validated with the analytical result. The maximum crack peak angle opening occurs at the range of loading of 16-160 KN which is 250, the stage that is able to cause pipe failure.